# (7-y)(7-y)=0

## Simple and best practice solution for (7-y)(7-y)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (7-y)(7-y)=0 equation:

Simplifying
(7 + -1y)(7 + -1y) = 0
Multiply (7 + -1y) * (7 + -1y)
(7(7 + -1y) + -1y * (7 + -1y)) = 0
((7 * 7 + -1y * 7) + -1y * (7 + -1y)) = 0
((49 + -7y) + -1y * (7 + -1y)) = 0
(49 + -7y + (7 * -1y + -1y * -1y)) = 0
(49 + -7y + (-7y + 1y2)) = 0
Combine like terms: -7y + -7y = -14y
(49 + -14y + 1y2) = 0
Solving
49 + -14y + 1y2 = 0
Solving for variable 'y'.
Factor a trinomial.
(7 + -1y)(7 + -1y) = 0
Subproblem 1Set the factor '(7 + -1y)' equal to zero and attempt to solve:
Simplifying
7 + -1y = 0
Solving
7 + -1y = 0
Move all terms containing y to the left, all other terms to the right.
Add '-7' to each side of the equation.
7 + -7 + -1y = 0 + -7
Combine like terms: 7 + -7 = 0
0 + -1y = 0 + -7
-1y = 0 + -7
Combine like terms: 0 + -7 = -7
-1y = -7
Divide each side by '-1'.
y = 7
Simplifying
y = 7
Subproblem 2Set the factor '(7 + -1y)' equal to zero and attempt to solve:
Simplifying
7 + -1y = 0
Solving
7 + -1y = 0
Move all terms containing y to the left, all other terms to the right.
Add '-7' to each side of the equation.
7 + -7 + -1y = 0 + -7
Combine like terms: 7 + -7 = 0
0 + -1y = 0 + -7
-1y = 0 + -7
Combine like terms: 0 + -7 = -7
-1y = -7
Divide each side by '-1'.
y = 7
Simplifying
y = 7Solutiony = {7, 7}`